Propagation of algal cultures using several media-mediated methods different implants (Journal of the College of Basic Education, 2022)
The study dealt with the process of algae propagation by various methods, due to the importance of algae in many fields through the use of its effective compounds in treatments and using it as a powder to adsorb pollutants, and this requires a large biomass. And the use of sterilized filtered wastewater from the secondary sedimentation basin before the stage of adding chlorine, and the use of one of the industrially prepared culture media with sterilized wastewater in a ratio of 1:1.